RNA Granules Living a Post-Transcriptional Life: the Trypanosomes' Case - Cassola, Alejandro (Current Chemical Biology, 2011)
Trypanosomes are protozoan parasites responsible for recalcitrant infectious diseases such as Sleeping sickness and Chagas disease in Africa and America, respectively. Their complex life-cycles are accompanied by alternation of forms specific of the insect vectors and vertebrate hosts, each with different metabolic and structural requirements. Unlike most other eukaryotes, these single-cell microorganisms seem to control the expression of protein-coding genes mostly by mRNA degradation, silencing and translation efficiency. Recent evidence showed that genuine cytoplasmic Stress Granules are formed as a response to heat stress in Trypanosoma brucei, basically formed by stalled translation initiation complexes on mRNA. On the other hand, Processing bodies (P bodies) are constitutive components of cytoplasmic mRNA metabolism in trypanosomes, which could have an important role in translational repression. During physiological starvation conditions in trypanosomes, components from P bodies fuse with other ribonucleoprotein complexes to form mRNA granules, where transcripts are stored and protected from degradation in a quiescent state. Other novel types of foci with unknown function that are related to RNA metabolism can be found in these parasites, namely heat-induced granules containing the 5' to 3' exoribonuclease XRNA, and starvation-induced granules containing transfer RNA halves. Thus, trypanosomes make use of non-membranous structures as a strategy to compartmentalize ribonucleoprotein complexes in the cytoplasm, aiding to cope with stressful situations avoiding mRNA translation or degradation. The relevance of stressinduced foci in trypanosomes has yet to be scored, although recent evidence suggests that these cytoplasmic organelles are required for survival under adverse growing conditions.
Keywords: Met-tRNA